2004
DOI: 10.1210/jc.2003-031764
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous and Endogenous Postprandial Lipid Abnormalities in Type 2 Diabetic Patients with Optimal Blood Glucose Control and Optimal Fasting Triglyceride Levels

Abstract: The aim of this study was to evaluate exogenous and endogenous lipoprotein responses to a standard fat-rich meal in type 2 diabetic patients with optimal fasting triglyceridemia and optimal blood glucose control. Seven type 2 diabetic patients and five nondiabetic controls (age, 49 +/- 7 and 48 +/- 4 yr; body mass index, 28.3 +/- 3.6 and 25.1 +/- 3.6 kg/m(2); mean +/- SD) were given, after at least 12 h of fasting, a standard fat-rich meal. Before and over the 6 h after the meal, serial blood samples were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 27 publications
10
33
1
8
Order By: Relevance
“…In type II diabetes, instead, the postprandial TG response may be a more direct index of chylomicrons and chilomicron remnants, which, in turn, derive directly from the amount and quality of dietary fat consumed. Moreover, the catabolism of these particles may be delayed in patients with diabetes (Taskinen, 2003;Rivellese et al, 2004), contributing, at least to some extent, to their higher postprandial TG levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In type II diabetes, instead, the postprandial TG response may be a more direct index of chylomicrons and chilomicron remnants, which, in turn, derive directly from the amount and quality of dietary fat consumed. Moreover, the catabolism of these particles may be delayed in patients with diabetes (Taskinen, 2003;Rivellese et al, 2004), contributing, at least to some extent, to their higher postprandial TG levels.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main features of diabetic dislypidemia is an increased and prolonged postprandial plasma lipid response, especially for TG (Taskinen, 2003;Iovine et al, 2004b;Rivellese et al 2004). As these postprandial abnormalities could partly explain the increased cardiovascular risk of type II diabetic patients (Taskinen, 2003), it may be very important to identify the main dietary determinants of postprandial TG response in these patients, in usual everyday life, to try to change dietary habits accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…2 Postprandial hypertriglyceridaemia is a distinct component of dyslipidaemia in T2DM 3,4 and is associated with CVD. 5,6 Two long-term prospective cohort studies recently showed that levels of nonfasting triglyceride independently and better predicts future cardiovascular events than levels of fasting triglyceride.…”
Section: Introductionmentioning
confidence: 99%
“…The latter are already accumulating in the absence of insulin-facilitated storage 50,51 . Similarly, in type 2 diabetes mellitus, increased insulin resistance leads to enhanced production and reduced clearance of TGs 52 . The causal role of diabetic ketoacidosis (DKA) in HTG was evaluated in a prospective study of 100 patients with DKA, 11 of whom had AP, and of these, HTG was the only attributable cause in 4 cases 53 .…”
Section: Secondary Causesmentioning
confidence: 99%